Digital Kazakhstan: achievements of tax administration of the Republic of Kazakhstan in the year of the 30th anniversary of independence (Journal of Economic Research & Business Administration, 2022)
The purpose of the research is to analyze the process of optimizing tax administration processes,determining its performance indicators and tools to influence them. Tax reforms are often the subject ofresearch in this direction. In the article, in the process of research, general scientific methods of cognitionwere used: dialectical, abstract-logical, analysis and synthesis, special research methods: analyticaland graphic approaches. The main results of the research include the following: 1) the scientific views,characteristics of simplified taxation based on the forecast were considered and systematized, and thecriteria for optimizing taxation processes were identified; 2) a model for making decisions on tax preferencesbased on information technologies is considered; 3) a comprehensive analysis of on-line receiptsof relevant information was carried out, which allows its automated analysis in various sections.The practical significance lies in the possibility of using the main conclusions in the activities of taxdepartments in the course of improving the methods and tools of tax administration, organizing interagencycooperation, and improving the quality of tax legislation. A set of traditional and innovative toolsof tax administration, which make it possible to improve its quality and efficiency, are of immediatepractical importance; models for building a tax information space by introducing a digital tax administrationsystem.Key words: tax administration, optimization of taxation processes, tax preferences, electronic digitalsignature.